The potential of alternative seed treatments to control anthracnose disease in white lupin. (August 2022) - Alkemade, J.A.; Arncken, C.; Hirschvogel, C.; Messmer, M.M.; Leska, A.; Voegele, R.T.; Finckh, M.R.; Kölliker, R.; Groot, S.P.C.; Hohmann, P.
Abstract: White lupin ( Lupinus albus L.) is a promising crop to meet the rising global demand for plant-based protein. The seed-borne pathogen Colletotrichum lupini, however, threatens lupin cultivation worldwide. Seed dressings using synthetic fungicides were shown effective to reduce infection levels, but their negative environmental impact and exclusion from organic production calls for more sustainable solutions. In this study, a total of eleven different alternative seed treatments were tested in field trials in Switzerland between 2018 and 2021. Treatment types consisted of: hot water, steam, electron, long-term storage, elevated partial pressure of oxygen (EPPO), vinegar, plant extracts and biological control agents (BCAs). The BCAs were tested for potential antagonistic activity against C. lupini during white lupin infection under controlled conditions prior to field trials. Long-term storage and vinegar treatments successfully reduced disease incidence and increased yield to levels similar to those observed for certified seeds, without significantly affecting germination rate. Although promising, effectiveness of these treatments needs further validation. Four BCAs showed significant disease reductions under controlled conditions. Besides lowering disease severity, two BCAs also reduced C. lupini DNA in stem tissue. These reductions, however, were not observed in the field, highlighting the importance of field validations. The treatments identified in this study provide a solid basis for the development of sustainable and effective seed protection strategies in white lupin to control C. lupini successfully. Highlights: Seed storage and vinegar reduce anthracnose incidence under on-farm field conditions. Certified seed is essential to limit primary anthracnose infection. High temperature seed treatments can severely affect germination rate.